2012
DOI: 10.1038/nphoton.2011.350
|View full text |Cite
|
Sign up to set email alerts
|

Comb-based radiofrequency photonic filters with rapid tunability and high selectivity

Abstract: Photonic technologies have received considerable attention for enhancement of radio-frequency (RF) electrical systems, including high-frequency analog signal transmission, control of phased arrays, analog-to-digital conversion, and signal processing. Although the potential of radio-frequency photonics for implementation of tunable electrical filters over broad RF bandwidths has been much discussed, realization of programmable filters with highly selective filter lineshapes and rapid reconfigurability has faced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
208
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(211 citation statements)
references
References 50 publications
1
208
0
2
Order By: Relevance
“…Equivalent configurations use dispersive optical fibre links (DOFL), with lengths up to 20 km (ref. 38), or dispersion-compensating fibres (DCFs) 23 .…”
Section: Implementation Of the Phc Delay Linementioning
confidence: 99%
See 1 more Smart Citation
“…Equivalent configurations use dispersive optical fibre links (DOFL), with lengths up to 20 km (ref. 38), or dispersion-compensating fibres (DCFs) 23 .…”
Section: Implementation Of the Phc Delay Linementioning
confidence: 99%
“…The salient features include: notch and band-pass operation; a footprint reduced by several orders of magnitude compared to filters based on FBG or fibre delay lines; broadband operation up to 50 GHz; and tunable free spectral ranges over 70 GHz. In addition, there is clear potential for the improvement of the selectivity, the main to secondary side-lobe (MSSL) ratio and the Q factor, thereby leading to highperformance MWP filtering owing to compatibility with sources of optical frequency combs 23 .…”
mentioning
confidence: 99%
“…Once, the time delay line if fabricated in FBGs tuning will be difficult. so tuning can be performed by tuning wavelength spacing .The tuning speed in laser array is in microsecond , faster tuning speed in the range of nanosecond can be achieve using optical comb , demonstration at speed of 40ns was reported [3]. It is observed that delay line microwave photonic filter operating incoherent regime with all positive coefficients operates as a low pass filter.…”
Section: Pc: Polarization Controllermentioning
confidence: 99%
“…Radio frequency (RF) filters based on optical frequency comb and dispersive propagation enable RF signal processing in the photonic domain [1,2]. Compared to its electrical counterpart, this approach is favored due to the broad bandwidth and low losses rendered by optical fibers, as well as arbitrary RF filter shape empowered by lineby-line shaping of the optical frequency comb [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to its electrical counterpart, this approach is favored due to the broad bandwidth and low losses rendered by optical fibers, as well as arbitrary RF filter shape empowered by lineby-line shaping of the optical frequency comb [2,3]. For instance, highly selective rectangular RF filter shape has been demonstrated using programmable pulse shapers to tailor optical frequency comb [4] or slice ASE source [5].…”
Section: Introductionmentioning
confidence: 99%